Visible thought : the new psychology of body language - Beattie, Geoffrey (Routledge, 2004)
Using diverse examples from the psychology lab, to Big Brother TV show, official Big Brother psychologist Geoffrey Beattie takes on the issue of what our everyday gestures mean and how they affect our relationships with other people.